2017
DOI: 10.1038/srep41611
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the smooth-coated otter (Lutrogale perspicillata): distinct evolutionary lineages and hybridization with the Asian small-clawed otter (Aonyx cinereus)

Abstract: We investigated the phylogeography of the smooth-coated otter (Lutrogale perspicillata) to determine its spatial genetic structure for aiding an adaptive conservation management of the species. Fifty-eight modern and 11 archival (dated 1882–1970) otters sampled from Iraq to Malaysian Borneo were genotyped (mtDNA Cytochrome-b, 10 microsatellite DNA loci). Moreover, 16 Aonyx cinereus (Asian small-clawed otter) and seven Lutra lutra (Eurasian otter) were sequenced to increase information available for phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
10
2
Order By: Relevance
“…The Asian small-clawed otter, Aonyx cinerea, was grouped with the smooth-coated otter, Lutrigale perspicillata, rather than the Asian clawless otter, Aonyx capenis. Although the previous studies reported that the Mustelinae is the closest subfamily of the Lutrinae (Moretti et al 2017), these results show that the Ictonychinae and Lutrinae were unresolved in a clade separate from the Mustelinae, Helictidinae, and Guloinae. These results based on mitochondrial genomic markers generally coincided with the previous studies (Koepfli et al 2008;Law et al 2018).…”
contrasting
confidence: 86%
“…The Asian small-clawed otter, Aonyx cinerea, was grouped with the smooth-coated otter, Lutrigale perspicillata, rather than the Asian clawless otter, Aonyx capenis. Although the previous studies reported that the Mustelinae is the closest subfamily of the Lutrinae (Moretti et al 2017), these results show that the Ictonychinae and Lutrinae were unresolved in a clade separate from the Mustelinae, Helictidinae, and Guloinae. These results based on mitochondrial genomic markers generally coincided with the previous studies (Koepfli et al 2008;Law et al 2018).…”
contrasting
confidence: 86%
“…Attempts initiated in 2003 towards restoration of the original habitat reversed the shrinking trend and marshes started to expand at the rate of 800 km 2 per year (Al-Ansari et al 2012). While the smooth-coated otter, along with the Eurasian otter Lutra lutra (Linnaeus, 1758) escaped extinction (Al-Sheikhly et al 2017;Moretti et al 2017) the fate of the long-tailed nesokia rat is more perplexing. The animal was last seen in 1976, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic reconstructions of Lg. perspicillata show that the above monophyletic clade already existed in the initial phase of the Early Pleis-tocene (Koepfli et al 2008;Moretti et al 2017). The species Le.…”
Section: Discussionmentioning
confidence: 89%